CALCULATION OF STRUCTURE SOIL RETAINING WALL TYPE CONTERFORT ON THE ROAD SECTION MARGASARI TO JONGGON KEC. LOA KULU KABUPATEN KUTAI KARTANEGARA - KUSNANTA, DEDI (KURVA S JURNAL MAHASISWA, 2014)
Road infrastructure is one of the veins and supporting the economic development of society , particularly in rural areas . Good road infrastructure to support economic development and even can be a driver in driving development.Landslide that occurred on the road or the road that experienced landslides, must be addressed so that it does not interfere with the performance of the road which is the lifeblood and driving force of development.From the calculation results can be concluded that the dimensions of the land pehanan wall is 3,5 meters high and 1 meter wide body length of 10 meters per segment , the stability of a retaining wall safe to bolster however affect the shear , so that the necessary foundation piles with additional bracing to the group pole to rigidify the structure of the walls and piles.